Microwave-assisted synthesis of few-layered TaTe2 and its application as supercapacitor - Chakravarty, Disha; Kumar, Praveen; Ugale, Vaishali S.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report a simple and rapid microwave-assisted synthesis of tantalum telluride (TaTe2) nanosheets. The ratio of tantalum pentachloride (TaCl5) and elemental tellurium (Te) powder were adjusted in the presence of NaBH4 in such a way as to obtain the TaTe2 nanosheet. The samples were characterized by various techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), UV/Vis spectroscopy, photoluminescence (PL) spectroscopy, and XRD. Our SEM, TEM, and AFM results show the formation of sheet-like morphology, while the XRD data confirms the high crystalline quality and stable phase of the TaTe2 formed. The supercapacitor cells were fabricated by using TaTe2 nanosheets as anode material, platinum metal wire as a counterelectrode, and Ag/AgCl as reference electrode. The calculated coulombic efficiency is more than 95%, while the cycle-to-cycle decrease in capacity is less than 5%. The maximum discharge or charging capacity is below 2.4 Wh/kg, which is an ideal characteristic for achieving supercapacitor behavior.
Keywords: Microwave chemistry; Nanostructures; Supercapacitors; Tantalum; Tellurium

Co-decorated tellurium nanotubes for energy storage applications - Bhol, Prangya; Swain, Swarnalata; Jena, Satyaranjan; Bhatte, Kushal; Rout, Chandra Sekhar; Saxena, Manav; Jadhav, Arvind H.; Samal, Akshaya K. (ACS Applied Nano Materials, 2021)
This paper explicitly discusses the synthesis of Co-decorated Te nanotubes (NTs) using Te NTs as the sacrificial template and the evaluation of their electrochemical performance. First, one-dimensional (1D) Te NTs were synthesized and characterized by spectroscopic and microscopic tools such as UV-visible spectroscopy, X-ray diffraction spectroscopy, X-ray photoelectron spectroscopy, field-emission scanning electron microscopy, high-resolution transmission electron microscopy, and energy-dispersive X-ray spectroscopy analyses. The as-prepared hexagonal Te NTs (h-Te NTs) possess diameters of about 35 +/- 5 nm and lengths of about 500 +/- 50 nm and were used for the synthesis of Co-decorated Te NTs. The 1D nanostructure with excellent conductivity enables the material to show excellent electrochemical performance. The asymmetric assembly of the CoTe-2//AC electrode material displayed a high specific capacitance of 147 F g(-1) (specific capacity, 162 C g(-1) at a current density of 2 A g(-1) in 4 M KOH electrolyte. In addition to that, the assembly of CoTe-2//AC achieved an excellent energy density of 51.1 W h kg(-1) at a power density of 2294 W kg(-1) and confirmed the as-synthesized Co-decorated Te NTs to be an excellent electrode material.
Keywords: cobalt; nanotubes; pseudocapacitors; surfactant; Tellurium; template